The Impact of a Pharmacist-Led Intravenous to Oral Switch of Metronidazole: A Before-and-After Study - Mahdi Algargoosh; Stephen Ritchie; Eamon Duffy; Bert Van der Werf; Mark Thomas; Nataly Martini (MDPI AG, 2022)
(1) Background. Intravenous (IV) to oral switch (IVOS) of antibiotics can reduce the length of hospitalisation, risk of IV catheter complications, and hospital costs. Pharmacists can play an instrumental role in implementing an IVOS initiative. The aim of this study is to evaluate the impact of pharmacist-led IVOS of metronidazole. (2) Method. This was an observational study conducted in a New Zealand hospital. During a 3-month intervention period, pharmacists identified patients receiving IV metronidazole; then initiated an IVOS for patients who met the criteria. The comparator groups were patients who were not switched by pharmacists in the post-intervention (post-IVOS) group, or patients treated with either IV or oral metronidazole prior to the intervention (pre-IVOS). Primary outcome measures were switch rate and duration of IV metronidazole treatment. Secondary outcome measures were readmission and/or repeat surgery within 90 days of discharge and the length of hospital stay. (3) Results. In total, 203 patients were included: 100 in the pre-IVOS and 103 in the post-IVOS groups. Pharmacists switched 63/93 (67.7%) of eligible patients to oral metronidazole in the post-IVOS period. Only 9/89 (10.1%) of IVOS eligible patients were switched in the pre-IVOS group. In the post-IVOS group, the mean duration of IV metronidazole treatment in patients switched by pharmacists was shorter than in those who were not switched by pharmacists (2.5 ± 2.8 days vs. 4.8 ± 5.9 days, p = 0.012). No significant difference was found in readmission or repeat surgery within 90 days of discharge for patients switched by pharmacists versus patients who were not switched by pharmacists. (4) Conclusion. Our data have demonstrated successful implementation of the hospital-approved pharmacist-led IVOS service.